Media literacy and fact checking: part two (Herald of Journalism, 2020)
This is the second part of the author’s study from the Michigan State University, devoted to the problems of identification and description of the disinformation crisis in the media and social media. The modern media field is increasingly filled with false information. The term “fake news” today in- cludes a wide range of manipulative technologies: “computational propaganda”, “puppet networks”, “troll armies”, anonymous source, alternative fact, gossip, deceit, rumors, false context, etc. Problems are exacerbated at a high pace. The development of technological processes and the shift in global com- munication discourse to social networks and the Internet.The purpose of the article is to study the history and evolution of the disinformation crisis, which is a serious threat to open societies around the world. The author proposes to activate critical thinking among young people, to teach the audience to intellectually recognize and process fake news, to understand the need for a critical and independent analysis of incoming news and background information.The author also believes that media literacy helps to understand the role of the media in society, as well as the acquisition of important research and expression skills needed by the audience. Media literacy skills also include the ability to access media, analyze content, evaluate messages, and create media for communication and expression. Learning how to verify facts is an important component of media literacy training, a way to protect against manipulation and fake news.
Keywords: media literacy, fact-checking, manipulation, propaganda, misinformation.